COVID-19 Dermatological manifestations. Presentation of two cases (Ozone Therapy Global Journal, 2020)
The coronavirus (COVID-19) is an emerging disease that was first reported in the city of Wuhan, China, last December 2020, which continues to spread throughout the world and has become an international public health alarm. COVID-19 was characterized as a "pandemic" by the World Health Organization (WHO) which has officially recognized that "there are currently no specific vaccines or pharmaceutical treatments available for COVID-19".1The authors submit two cases of COVID-19 that debuted with skin lesions and that were treated in an adjuvant way; the first with rectal insufflations and the second with ozonized saline solution (O3SS). Ozone therapy was chosen as a complementary treatment, as it has an anti-inflammatory, antithrombotic and antihypoxic character. Three characteristics with which the disease occurs.2The evolution of the patients was managed on an outpatient basis without complications and took place in a short period (5 to 7 days), which was accompanied by the improvement of clinical, immunological, biochemical and hematological indicators. No adverse events were observed during treatment. This case report is indicative of the likely efficacy of these complementary treatments and it is recommended that larger clinical studies be conducted that can demonstrate the benefits of these treatments